Assembly of metallic nanoparticle arrays on glass via nanoimprinting and thin-film dewetting - Sun-Kyu Lee; Sori Hwang; Yoon-Kee Kim; Yong-Jun Oh (Beilstein Journal of Nanotechnology, 2017)
We propose a nanofabrication process to generate large-area arrays of noble metal nanoparticles on glass substrates via nanoimprinting and dewetting of metallic thin films. Glass templates were made via pattern transfer from a topographic Si mold to an inorganically cross-linked sol–gel (IGSG) resist on glass using a two-layer polydimethylsiloxane (PDMS) stamp followed by annealing, which turned the imprinted resist into pure silica. The transparent, topographic glass successfully templated the assembly of Au and Ag nanoparticle arrays via thin-film deposition and dewetting at elevated temperatures. The microstructural and mechanical characteristics that developed during the processes were discussed. The results are promising for low-cost mass fabrication of devices for several photonic applications.